Aleitamento materno em crianças com microcefalia por síndrome congênita do vírus Zika - Karole Brito Alves Costa; Normeide Pedreira dos Santos França (Sociedade Brasileira de Pediatria, 2023)
INTRODUCTION: Children with microcephaly are at increased risk for global developmental delay, physical and intellectual disability, and sensorineural changes. Records on growth and development, as well as records on the prevalence of breastfeeding, are still scarce in this population. OBJECTIVE: To identify duration and characterization of breastfeeding in children with microcephaly due to congenital ZIKV syndrome (SCZV) seen at a referral service. METHODOLOGY: Descriptive, cross-sectional, quantitative study. Data collection was performed on medical records and during interviews, using standardized questionnaires, during the months of September and November 2019. Descriptive statistical analysis was performed using the SPSS 25.0 program. RESULTS: Fourteen children met the inclusion criteria and were included in this study. The average age was 43 months (20-50), and the average head circumference corresponded to 29.85 cm (25-34). Most children (92.9%) were breastfed. Eight children (57.2%) received exclusive breastfeeding and five (35.7%) received predominant breastfeeding. Only 21.4% suckled in the first hour of life. The mean time of BF was 14.67 months (04-37). Twelve mothers had already weaned during the data collection period. Three (21.4%) underwent gradual weaning and nine (64.3%) underwent abrupt weaning. All children used artificial teats (pacifiers, n = 14; baby bottles, n = 13), and in 50% of cases, this use occurred while still in the maternity ward. CONCLUSION: This study found a prevalence of 92.9% of breastfed children within the studied group, and an average duration of breastfeeding less than 2 years of age.